Novel rhesus macaque immunoglobulin germline genes identified by three sequencing approaches - Guo, Yicheng; Waltari, Eric; Lu, Hong; Sheng, Zizhang; Wu, Xueling (Frontiers in Immunology, 2024)
IntroductionRhesus macaques have long been a focus of research for understanding immune responses to human pathogens due to their close phylogenetic relationship with humans. As rhesus macaque antibody germlines show high degrees of polymorphism, the spectrum of database-covered genes expressed in individual macaques remains to be determined.MethodsHere, four rhesus macaques infected with SHIVSF162P3N became a study of interest because they developed broadly neutralizing antibodies against HIV-1. To identify the immunoglobulin heavy chain V-gene (IGHV) germlines in these macaques, we applied three sequencing approaches – genomic DNA (gDNA) TOPO sequencing, gDNA MiSeq, and messenger RNA (mRNA) MiSeq inference with IgDiscover, and illustrated the detection power of each method.ResultsOf the 197 new rhesus IGHV germline sequences identified, 116 (59%) were validated by at least two methods, and 143 (73%) were found in at least two macaques or two sample sources. About 20% of germlines in each macaque are missing from the current database, including a subset frequently expressed. Overall, gDNA MiSeq determined the greatest number of germline sequences, followed by gDNA TOPO sequencing and mRNA MiSeq inference by IgDiscover, with IgDiscover providing direct evidence of allele expression and usage.DiscussionOur interdisciplinary study sheds light on germline sequencing, enhances the rhesus IGHV germline database, and highlights the importance of germline sequencing in rhesus immune repertoire studies.